Aging and KIBRA/WWC1 genotype affect spatial memory processes in a virtual navigation task. Issue 10 (26th June 2013) - Schuck, Nicolas W.; Doeller, Christian F.; Schjeide, Brit‐Maren M.; Schröder, Julia; Frensch, Peter A.; Bertram, Lars; Li, Shu‐Chen
ABSTRACT Spatial navigation relies on multiple mnemonic mechanisms and previous work in younger adults has described two separate types of spatial memory. One type uses directional as well as boundary‐related information for spatial memory and mainly implicates the hippocampal formation. The other type has been linked to directional and landmark‐related information and primarily involves the striatum. Using a virtual reality navigation paradigm, we studied the impacts of aging and a single nucleotide polymorphism (SNP rs17070145) of the KIBRA gene (official name: WWC1) on these memory forms. Our data showed that older adult's spatial learning was preferentially related to processing of landmark information, whereas processing of boundary information played a more prominent role in younger adults. Moreover, among older adults T‐allele carriers of the examined KIBRA polymorphism showed better spatial learning compared to C homozygotes. Together these findings provide the first evidence for an effect of the KIBRA rs17070145 polymorphism on spatial memory in humans and age differences in the reliance on landmark and boundary‐related spatial information. © 2013 Wiley Periodicals, Inc.